Five novel cis-regulatory deletions of SOX10 cause Waardenburg syndrome type II - Huang, Yu; Geng, Jia; Long, Yang; Xiong, Wenyu; Kang, Lu; Chen, Meilin; Tang, Ting; Zhong, Mingjun; Bu, Fengxiao; Lu, Yu; Cheng, Jing; Yuan, Huijun (Frontiers in Audiology and Otology, 2024)
Introduction Waardenburg syndrome (WS) is a genetic disorder characterized by hearing loss, hypopigmentation, and distinct facial features. Despite > 60% molecular diagnosis rate for WS patients, pathogenic variants within coding regions are predominant, with few non-coding copy number variations (CNVs) reported. Methods In this study, we performed whole genome sequencing (WGS) on 59 undiagnosed WS patients and analyzed the CNVs within the promoter and enhancer regions of the SOX10 gene. Results We identified five novel pathogenic deletions ranging from 448 bp to 70 kb upstream of SOX10. Two deletions were in the enhancer region, while three were in the promoter and 5'UTR region. These CNVs manifested as WS type II in eight patients from five unrelated families, demonstrating phenotypic heterogeneity. Furthermore, analysis of CNV1 within the enhancer region suggested a potential mechanism involving Alu-mediated non-allelic homologous recombination (NAHR). Conclusion Our findings extend the mutation spectrum of the SOX10 gene and elucidate the pathogenic role of CNVs in cis-regulatory elements, particularly variations in enhancer and promoter regions, thereby enhancing clinical gene detection and interpretation of non-coding regions.